Emerging helminthiases of song thrush (Turdus philomelos) in Central Europe - Sitko, Jiljí; Heneberg, Petr (Parasitology research, 2020)
Turdus philomelos is a common Western Palearctic thrush species of forests and agricultural landscapes, where it relies on the presence of hedgerows, patches of trees, and shrubs. In the present study, we address long-term changes in component communities of trematodes in T. philomelos across the timespan of over half a century. Based on our preliminary observations, we hypothesized that component communities of trematodes in T. philomelos in the study area are more diverse and species-rich compared with several decades ago. In the 1961-2019, we performed full-body necropsies of T. philomelos, which originated from the southern Czech Republic, and examined them for the presence of trematodes. We compared the trematode species richness and diversity of the analyzed component communities. The number of trematode species per host steadily increased in time in adult females and males. In juveniles, the highest numbers of trematode species per host were reached already in 1961-1990, then dropped and slowly raised up again in the latter time periods. The newly accumulated evidence suggests that trematodes with intermediate hosts previously restricted to T. philomelos wintering grounds increased in abundance in the study area. Some of them (Morishitium polonicum, Psilotornus confertus) sporadically appeared in juveniles or first-year birds, from which they were previously completely absent. Some of the spreading species, such as Lutztrema attenuatum, are present in high prevalence and high intensities of infection. Yet unknown part of observed changes could be related to changes in food composition; however, direct evidence for changes in T. philomelos diet is lacking despite clear evidence for a decline in earthworms in agricultural landscapes.
Keywords: Animals; Helminthiasis, Animal; Czech Republic; zpěvní ptáci; helmintózy zvířat; zvířata; Ecological Parameter Monitoring; Songbirds; Female; Male; ekosystém; sledování ekologických parametrů; Ecosystem; Trematoda; Česká republika; Bird Diseases; nemoci ptáků; ženské pohlaví; mužské pohlaví